Multicenter Study Evaluating Nitrous Oxide Use for Labor Analgesia at High- and Low-altitude Institutions. Issue 3 (24th September 2022) - Wood, C.; Arbet, J.; Amura, C.; Nodine, P.; Collins, M.; Orlando, B.; Mayer, D.; Stein, D.; Anderson, J.
Abstract : ( Anesth Analg . 2022;124:294–302) The United States has used nitrous oxide as a labor analgesia since the 1940s because it has no impact on uterine myometrial contractility, it has little impact on maternal hemodynamics and respiration, and it is a noninvasive procedure. However, most medical professionals still prefer neuraxial analgesia. Previous studies report that 40% nitrous oxide successfully decreased pain and increased maternal satisfaction during labor compared with a placebo at sea level, but there are no studies evaluating the effect of nitrous oxide on maternal pain relief or satisfaction in high altitudes. Because of the partial pressure gas law, as elevation increases, the study hypothesized gas analgesia administration had less of an effect than at sea level, both in pain relief and side effects. This study evaluated altitude's effect on nitrous oxide administration by comparing high altitude and low altitude births.